Burnout in officers of the prison service units. The role of personality and selected professional characteristics - Ewa Sygit-Kowalkowska; Magdalena Weber-Rajek; Martyna Herkt; Roman Ossowski (Nofer Institute of Occupational Medicine, 2017)
Background: The researchers involved in the studies of burnout indicate its 3 sources: the structure of the personality, the specificity of interpersonal relationships, and the organizational factors. The aim of this study was to evaluate the occurrence of burnout and personality characteristics of prison officers, as well as to determine predictors of burnout in this occupational group. Material and Methods: The study was conducted among prison officers, who were divided into 2 groups, the officers working in direct contact with prisoners (group I) and those employed in the prison administration (group II). The study used 2 tools: NEO-Five Factor Inventory (NEO-FFI) and Link Burnout Questionnaire (LBQ). Results: Analysis of personality traits in the study group showed high severity traits of neuroticism, extraversion, openness, agreeableness and conscientiousness. However, the best results were obtained in terms of extraversion and the lowest in the range of conscientiousness. The level of burnout in both groups was found to be within the upper limit of the average results, without statistically significant differences between the groups. The results showed that people working in direct contact with prisoners experience greater disappointments and psychophysical exhaustion at work. The analyses showed that the level of exhaustion and disappointment of the employees surveyed increases with increasing seniority. It was also shown that the level of neuroticism, extraversion and agreeableness is the predictor of effectiveness. Conclusions: The level of burnout in the study group falls within the upper limit of the average results. Personality traits are an important determinant for the development of symptoms of burnout in the penitentiary officers, and their role changes over the years of continuous prison service. The position at work diversifies the degree of experiencing symptoms of burnout. Med Pr 2017;68(1):85-94